Pelatihan Pembuatan Aplikasi Android Evaluasi Pembelajaran Biologi Berbasis PowerPoint Pada Guru Biologi Sekolah Menengah - Guntur Nurcahyanto; Erna Kurniawati; Nabilla Riska Nurjannah (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2022)
The rapid development in the field of information technology (IT) makes there many variations that are more interactive and as an alternative to avoiding student cheating when doing multiple choice questions or essay questions that allow teachers to make assessments at the end of learning materials to be more accurate, fast and efficient. Based on the results of initial observations and previous research, the factor of the lack of knowledge of mastery of technology in high school teachers will have an impact on the delay in following the development of technology and information that is so very fast that it affects the transfer of information that is inefficient and effective, especially in the aspect of teacher assessment of students. One of the applications of information technology is the Android Based Test (ABT). For the learning evaluation to run well, teachers must make a more efficient and innovative evaluation tool using the PowerPoint-based learning evaluation android application. This is so that teachers can conduct more accurate learning evaluations and avoid student cheating. Students can directly use cell phones to evaluate questions if school facilities for computer use are inadequate. The solution offered is by conducting training on making an android application for evaluating biology learning based on PowerPoint. The activity method is the face-to-face tutorial learning method with the training participants. The results of this activity showed that the participants were able to make excellent android-based applications and could function properly. Although there are obstacles, such as the participants, have not prepared various questions according to the subjects being taught. This training can provide understanding and expertise in making information technology-based evaluation tools for teachers.